Efficient filtration of acid-decomposed Kyzylkum and Karatau phosphate blends - Elyor, Eminov; Kurniawan, Tonni Agustiono; Kholtura, Mirzakulov; AbdulKareem-Alsultan, G. (Springer Science and Business Media Deutschland GmbH, 2026)
This study investigates the extraction of H₃PO₄ from mixtures of Karatau phosphorite (KP) and washed burned concentrated Central Kyzylkum phosphorite (WBC CKP) at varying ratio combinations (70:30 to 30:70). The chemical compositions of both raw and treated phosphorites were determined using physicochemical analytical methods. The effects of reaction duration, temperature and different acid concentrations on the rate of decomposition and pulp filtration behaviour were systematically tested. Concentrated sulfuric acid (93%) and a diluted circulating phosphoric acid solution (12% (v/v) P₂O₅) were applied as the reaction medium for ore decomposition. The resulting extraction pulp was filtered and subjected to a three-stage washing process, designed to minimise P₂O₅ losses in the phosphogypsum residue. A comprehensive material balance was developed based on the experimental data, confirming high phosphorus recovery and demonstrating that the residual water-soluble P₂O₅ in the final washed gypsum did not exceed 1.9%. Additionally, the rheological properties of the acid pulps were analysed at different ore ratios, with the 30:70 KP to WBC CKP mixture showing optimal filtration characteristics and decomposition efficiency. The established material balance and kinetic data provide a basis for improving the efficiency and sustainability of industrial phosphoric acid production from regional phosphate resources.